Comparative effect of Indium/Molybdenum/ Strontium doping on structural, vibrational and optical properties of ZnO sprayed thin films - Shaiboub, Ramadan E. Shaiboub; Boucherou, Nacer Boucherou; بوشروي, ناصر بوشروي; Ziouche, Aicha Ziouche; Boukhachem, Abdelwaheb Boukhachem; Amlouk, Mosbah Amlouk (Sharwes Scientific Journal, 2025)
Zinc oxide (ZnO) thin films were deposited on glass substrates using a simple microspray technique, and some of the resulting films were doped with strontium, indium, and molybdenum at molar concentrations of 1%. In addition to classical structural studies, such as X-ray diffraction (XRD) patterns, which revealed peaks corresponding to hexagonal zinc oxide wurtzite, topographical observations using atomic electron microscopy (AFM), and vibrational properties using Raman spectroscopy with excitation wavelengths at 488 nm where the FWHM value for Raman spectroscopy was approximately 15 cm-1, comprehensive optical measurements were also performed using photothermal techniques. The dispersion properties of the differently doped layers were derived from their transmittance and reflectance spectra over an extended wavelength range. The Raman shift E1(LO) mode was found to decrease with the oxidation number of the doping elements. The shift was found to be a positive factor with peaks almost the same in energy as the Urbach energy. Finally, the analysis of the refractive index using the Urbach-Martinsen model allowed for the nanoscale explanations for the variation in the doping-related evolution of the Urbach tails. The Urbach coefficients were calculated, and the results showed that the photothermal expansion decreases with increasing oxidation number of the doped elements. The optical properties of the refractive index were also calculated, and it was also observed that it decreases with wave length.